Humean elements in the teachings of Ito Jinsai - Ogrizek, Marko (Asian studies, 2023)
The present article juxtaposes selected elements of the Humean position on moral mo-tivation with the ethical teachings of the Edo period Japanese Confucian scholar Ito Jinsai—especially the latter’s critical reading of the notion of structural coherence li, his defence of human feelings as the fundamental ground of moral motivation and his views on the origins of moral sentiment. In doing so, the article aims to show that there is an interesting line going through Jinsai’s work that might be argued to bear, within the philosophical project of Confucian ethics, similarities to certain of Hume’s more famous positions, which it actually predates.
Keywords: David Hume; Ito Jinsai; moral motivation; moralna motivacija; sentimentalism; sentimentalizem; structural coherence li; strukturna koherenca li